We, Them, and It: Dictator Game Offers Depend on Hierarchical Social Status, Artificial Intelligence, and Social Dominance - Weiß, Martin; Rodrigues, Johannes; Paelecke, Marko; Hewig, Johannes (Frontiers in Psychology, 2020)
We investigated the influence of social status on behavior in a modified dictator game (DG). Since the DG contains an inherent dominance gradient, we examined the relationship between dictator decisions and recipient status, which was operationalized by three social identities and an artificial intelligence. Additionally, we examined the predictive value of social dominance orientation (SDO) on the behavior of dictators towards the different social and non-social hierarchical recipients. A multilevel model analysis showed that dictator recipients with the same status as the dictator benefited the most and the artificial intelligence the least. Furthermore, SDO, regardless of social status, predicts behavior towards recipients in such a way that higher dominance is associated with lower dictator donations. In summary, people treat other people of higher and lower status equally, those of equal status better and, above all, an algorithm worst. The large proportion of female participants and the limited variance of SDO should be taken into account with regard to the results of individual differences in SDO.